2022
DOI: 10.1111/psyg.12849
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant‐induced serotonin syndrome in older patients: a cross‐sectional study

Abstract: Background Widespread prescription of antidepressants and their resulting role in serotonin syndrome (SS) are of great importance for clinical practice in the elderly. This study aims to investigate possible associations of antidepressant drug‐induced SS with related variables in these patients. Methods A total of 238 older adults using antidepressants were included. Patients who fulfilled the Hunter Serotonin Toxicity Criteria (HSTC) for SS were considered as the clinical groups (mild, moderate, or severe), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The syndrome is more commonly reported among elderly patients. In a recent study, 2 Erken et al found that 25.2% (60 out of 238 participants) of elderly patients taking antidepressants resulted in serotonin syndrome, and at least two-thirds (68.3%) of these patients showed potentially life-threatening symptoms. Women were twice as likely as men to have serotonin syndrome, with the most common diagnostic findings in these patients being tremor and hyperreflexia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The syndrome is more commonly reported among elderly patients. In a recent study, 2 Erken et al found that 25.2% (60 out of 238 participants) of elderly patients taking antidepressants resulted in serotonin syndrome, and at least two-thirds (68.3%) of these patients showed potentially life-threatening symptoms. Women were twice as likely as men to have serotonin syndrome, with the most common diagnostic findings in these patients being tremor and hyperreflexia.…”
Section: Discussionmentioning
confidence: 99%
“…S-ketamine has the advantages of a stronger analgesic effect, fewer psychomotor side effects, a faster clearance rate, and fast recovery time than racemic ketamine. 2 The general reaction to intravenous injection of S-ketamine ranges from mild lightness or irritability to more obvious reactions like losing control, visual illusions, ideological disorders, or delusional thinking. 3 However, our latest network meta-analysis has shown the potential preventive effects of ketamine on cognitive impairment after surgeries.…”
Section: Cognitive Decline After S-ketamine Usementioning
confidence: 99%
See 1 more Smart Citation
“…Only 0.09% of patients (4 out of 4538) had SS[ 19 ]. Erken et al [ 25 ] examined 234 elderly patients (over 60 years old) who were taking antidepressants and had been admitted to a geriatric department. Sixty patients (25%) fulfilled Hunter criteria for SS[ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Erken et al [ 25 ] examined 234 elderly patients (over 60 years old) who were taking antidepressants and had been admitted to a geriatric department. Sixty patients (25%) fulfilled Hunter criteria for SS[ 25 ]. Di Salvo et al [ 27 ] studied 133 consecutive patients who were admitted to the psychiatric inpatient unit and were using at least one serotonergic medication.…”
Section: Introductionmentioning
confidence: 99%